2023
DOI: 10.3390/v15020384
|View full text |Cite
|
Sign up to set email alerts
|

Molnupiravir and Nirmatrelvir/Ritonavir: Tolerability, Safety, and Adherence in a Retrospective Cohort Study

Abstract: Background. Molnupiravir (MOL) and nirmatrelvir/ritonavir (NIR) were recently approved for the early treatment of COVID-19, but real-life data on tolerability, safety, and adverse events (AEs) are still scarce. Methods. We conducted a retrospective cohort study including all patients who were prescribed MOL and NIR at the Infectious Diseases Unit of Padua University Hospital, between January and May 2022. Demographic, clinical, and safety variables were recorded. Results. We included 909 patients, 48.3% males … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 18 publications
3
20
0
Order By: Relevance
“…Our experience of oral antiviral in the early treatment of COVID-19 is available elsewhere. 33 Remdesivir was administered intravenously in the outpatient's clinic at the dosage of 200 mg the first day, followed by 100 mg/daily for other 2 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our experience of oral antiviral in the early treatment of COVID-19 is available elsewhere. 33 Remdesivir was administered intravenously in the outpatient's clinic at the dosage of 200 mg the first day, followed by 100 mg/daily for other 2 days.…”
Section: Methodsmentioning
confidence: 99%
“…Patients who received a concomitant treatment with oral antiviral agents nirmatrelvir/ritonavir or molnupiravir, or monoclonal antibodies were excluded, since our aim was to assess the outcome for the early antiviral intravenous option. Our experience of oral antiviral in the early treatment of COVID‐19 is available elsewhere 33 . Remdesivir was administered intravenously in the outpatient's clinic at the dosage of 200 mg the first day, followed by 100 mg/daily for other 2 days.…”
Section: Methodsmentioning
confidence: 99%
“…Four studies 19,28,29,31 involving 1679 patients reported the incidence of adverse events leading to treatment discontinuation. The pooled estimate showed no significant difference between the two treatment groups in terms of incidence of adverse events leading to treatment discontinuation (OR = 1.18, 95% CI: 0.69–2.00, p = 0.53, I 2 = 10.15%) (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies 19,28,29,31 involving 1679 patients reported the incidence of adverse events leading to treatment discontinuation.…”
Section: Adverse Events Leading To Treatment Discontinuationmentioning
confidence: 99%
See 1 more Smart Citation